Peranan E-Commerce dalam Transaksi Salam - Salsabila, Siti Afifah; Maulana, Muhammad Irvan; Nasution, Siti Zahra Amelia Putri; Tyrta, Arya Wangsa; Aginta, Gadis; Siregar, Pani Akhiruddin (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
E-commerce has become one of the important innovations in facilitating the implementation of the salam contract, a sharia-based transaction in which payment is made in advance for goods to be delivered at a later date. With features such as pre-orders, digital payment systems, and logistics management, e-commerce platforms enable salam transactions to be carried out more transparently, efficiently, and in accordance with sharia principles. In addition, the wide market reach in e-commerce provides opportunities for business actors, especially MSMEs, to expand access to their products nationally and internationally. However, the implementation of the salam contract in e-commerce faces a number of challenges, such as late delivery of goods and the potential for unclear product specifications. To overcome this problem, the integration of technologies such as increased sharia supervision are important solutions. With further optimization, e-commerce can act as a catalyst in supporting the development of the sharia economy in the digital era. This study shows that e-commerce not only facilitates transactions, but also has the potential to strengthen trust and inclusivity in sharia-based trade.